Consumption of kiwifruit capsules increases Faecalibacterium prausnitzii abundance in functionally constipated individuals: a randomised controlled human trial. (12th October 2017) - Blatchford, Paul; Stoklosinski, Halina; Eady, Sarah; Wallace, Alison; Butts, Christine; Gearry, Richard; Gibson, Glenn; Ansell, Juliet
Abstract: This study investigated the impact of ACTAZIN™ green (2400 and 600 mg) and Livaux™ (2400 mg) gold kiwifruit supplements on faecal microbial composition and metabolites in healthy and functionally constipated (FC) participants. The participants were recruited into the healthy group ( n 20; one of whom did not complete the study) and the FC group ( n 9), each of whom consumed all the treatments and a placebo (isomalt) for 4 weeks in a randomised cross-over design interspersed with 2-week washout periods. Modification of faecal microbiota composition and metabolism was determined by 16S rRNA gene sequencing and GC, and colonic pH was calculated using SmartPill ® wireless motility capsules. A total of thirty-two taxa were measured at greater than 1 % abundance in at least one sample, ten of which differed significantly between the baseline healthy and FC groups. Specifically, Bacteroidales and Roseburia spp. were significantly more abundant ( P < 0·05) in the healthy group and taxa including Ruminococcaceae, Dorea spp. and Akkermansia spp. were significantly more abundant ( P < 0·05) in the FC group. In the FC group, Faecalibacterium prausnitzii abundance significantly increased ( P = 0·024) from 3·4 to 7·0 % following Livaux™ supplementation, with eight of the nine participants showing a net increase. Lower proportions of F. prausnitzii are often associated with gastrointestinal disorders. The discovery that Livaux™ supplementation increased F. prausnitzii abundance offers a potential strategy for improving gut microbiota composition, as F. prausnitzii is a butyrate producer and has also been shown to exert anti-inflammatory effects in many studies.